Peningkatan Minat Baca Dan Kunjungan Perpustakaan Aneka Ilmu Melalui Program KKN Di Desa Bogor Baru - Syafitri, Alya Novia; Amanda, Kiki Rizki; Saragih, Rosa Sri Andari; Muhammad Ravie; Syafira Dwi Wulandari; Deo Surya Anjaya; Dival Satria Gunawan; Bilal Chairul Ahmad; Rustikawati (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Reading interest in rural communities is often hindered by limited access to books and a lack of engaging literacy programs. This study aims to quantitatively measure the increase in reading interest and visits to the "Aneka Ilmu" library in Bogor Baru Village through a Community Service Program (KKN) intervention. The research method used a quantitative approach by comparing library visitor data before and during the KKN period. Visitor data were recorded and analyzed descriptively based on age groups and gender. Results showed a significant increase in the number of library visitors, amounting to 150% compared to the previous period. The largest increase was observed in the 7-12 age group, with a 300% increase, and was predominantly female with a 240% increase. The conclusion of this study is that a structured and innovative literacy program can quantitatively increase reading interest and community participation, especially among children, in literacy activities at a village library.